Ambiente construído e vitalidade urbana: avaliação de três praças do bairro Manaíra - Duarte, Juliana de Souza (2014)
This research investigates the relation between use and form in three public squares (praças) of João Pessoa, Paraíba, Brasil: Praça Sílvio Port, Praça Alcides Carneiro and Praça Chateaubriand Arnaud. The three squares are located in the same neighborhood Manaíra. By choosing three squares in the same neighborhood, some variables remain fixed, such as geographical location in relation to the city limits and the socioeconomic profile of the resident population. On the other hand, hey have distinct spatial configurations, which result into different types and intensities of uses. The aim of this work is to identify the relationship of the physical and spatial attributes of the squares and their surroundings, with their use, using concepts of urban design and universal (inclusive) design as a reference. Thematic maps to analyze the variables were developed: number of lots, land use in lots, access roads and population. The observation and mapping of the users was also carried out to identify the amount of activities and people in the square. The results show that there are differences in the intensity of use and the types of predominant activities in the three squares, and associated with this there are also differences in the characteristics of the squares and their surroundings. By identifying these relationships, this piece of research can serve as a reference basis for the planning and implementation of new squares, as well as renovations and redevelopment of these spaces.